1996
DOI: 10.1021/ef9500898
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of N2O Formation from Char Combustion

Abstract: This paper describes an experimental study on N2O and NO x emission from char combustion. Experiments have been carried out in a fixed bed reactor in the temperature range of 973−1323 K. Oxygen concentrations for combustion, temperature, and char type have been found to have strong effects on both N2O and NO x emissions. With an increasing temperature, N2O reaches a peak at 1073 K and then decreases with temperature. At the same time NO x remains nearly the same. When oxygen concentration increases, the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 6 publications
2
19
0
Order By: Relevance
“…As in this work the experiments were carried out in an inert atmosphere, the main reduction reactions will occur via homogeneous mechanisms. N 2 O and N 2 , reduced species that contribute to m/z 14, will be produced from the oxidation of HCN by NO in the gas phase [30].…”
Section: Temperature-programmed Pyrolysismentioning
confidence: 99%
“…As in this work the experiments were carried out in an inert atmosphere, the main reduction reactions will occur via homogeneous mechanisms. N 2 O and N 2 , reduced species that contribute to m/z 14, will be produced from the oxidation of HCN by NO in the gas phase [30].…”
Section: Temperature-programmed Pyrolysismentioning
confidence: 99%
“…The results of the latter investigators include not only char-N oxidation, but also char-N conversion by other reactions, for example, the reaction of NO with char-N. NO has been found to improve the conversion of char-N to N,O (Tullin et al 1993;Feng et al 1994b). So, during the combustion of char in fluidized beds, N,O formation can be split into two parts: one from the direct oxidation of char-N (de Soete, 1990;Feng et al 1994a), the other from the reaction of NO with char-N, (Tullin et al 1993;Feng et al 1994b). …”
Section: Mechanisms O F No Formation and Destructionmentioning
confidence: 99%
“…A rough indication of the contribution of the above mechanisms to N,O emission is also given in Figure 1. The estimate is based on the experimental results, (Feng et al 1994b). For this coal (GL coal in Feng et al, 1994b), more than 60% of the N,O emission comes from char combustion.…”
Section: Mechanisms O F No Formation and Destructionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, however, N 2 O formation becomes larger at a lower combustion temperature in CFB. It has been reported that the reaction of NO and char-N with O 2 becomes the main pathway for N 2 O formation when NO is included in the inlet gases [13].…”
Section: Introductionmentioning
confidence: 99%